Identificación de las patologías de los órganos genitales de las vacas faenadas en el camal municipal de la ciudad de Zamora - Pineda Íñiguez, Jorge Fernando (2016)
The aim of this study was to determine the alterations of the genital tract of female cattle slaughtered in the municipal slaughterhouse in the city of Zamora, according to the following variables: race, age, origin, and within these parameters, pregnant animals, and abnormalities more frequent in the female reproductive slaughtered in the municipal slaughterhouse in the city of Zamora, the size of the sample was 190 apparatus genital tracts slaughtered bovine females of reproductive age, for which a simple random sampling was performed; in order to determine the changes or more frequent macroscopic changes according to the study variables raised, in which the following results were mainly located: females showed no problem on the reproductive tract of a total of 147 representing 77 % of the total sample; animals with pathological changes in the reproductive system a total of 43 corresponding to 23% of the sample; for data analysis SPSS 1.9 in which frequency tables are analyzed, determining the number and percentage of cases found, also regression tests were performed to determine the possible correlation between the variables studied and pathologies used found. Among the most important changes are highlighted: changes in the vagina and vaginal vestibule (65%); changes in the ovaries (13.9%); changes in the uterus (11.5%); alterations in the oviducts (9.3%); vulvovaginitis 32.5% and 32.5% genital hypoplasia age females of bovine animals slaughtered ranges ≤ 4 years> 4 years being concerned about the high number of slaughtered females of reproductive age.